Review of the Orphninae (Coleoptera: Scarabaeidae) of Sri Lanka, with description of a new species of genus Orphnus Macleay, 1819 - Frolov, Andrey V.; Akhmetova, Lilia A. (European Journal of Taxonomy, 2021)
The scarab beetles of the subfamily Orphninae (Coleoptera: Scarabaeidae) from Sri Lanka are reviewed. Four species of the genus Orphnus Macleay, 1819, are recorded from the island: O. bicolor (Fabricius, 1801), O. parvus (Wiedemann, 1823), O. mysoriensis Westwood, 1845, and O. medvedevi sp. nov. Lectotypes are designated for the three former names. Synonymy of O. detegens Walker, 1859, and O. scitissimus Walker, 1859, is discussed. Keys, illustrations of habitus and male genitalia, and distributional record maps are given for all species.